(untitled) - MANJUNATH D.R (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Employability denotes skills and attributes that make an individual desirable to potential employers. Owing to the dramatic increase in enrollment rate of higher education, a diploma is no longer a guarantee of employment and higher education institutes are expected to equip students with employability skills and attributes. However, the mandatory inclusion of employability skills and attributes in higher education has provoked considerable debate and controversy. Although the connection between employability and employment is well documented, it is not clear whether employability skills have potential impacts on academic performance of graduate students. This study is an attempt to further such research work and analyze whether good academic performance ensures employability. The research is an outcome of the data collected out of a series of pool campus drives conducted. The hypthesis was tested using ANOVA and T-test. The results show that very high academic performance does indeed lead to employability. In addition it was also seen that this set of students by and large also had the soft skills that companies look for while hiring candidates.